2017
DOI: 10.1108/jcp-09-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Policing people with sexual convictions using strengths-based approaches

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
(49 reference statements)
2
20
0
Order By: Relevance
“…In addition, this present study was able to reach beyond the scope of the Nicholls and Webster pilot study, as we also examined subsequent risk management plans. It is perhaps unsurprising we found problems in the quality of ARMS assessments, as in our earlier study, exploring police practitioners' experiences of completing ARMS assessments (Kewley, 2017); practitioners reported several issues with both the tool, and their own capacity to complete the assessment. Practitioners felt their training and supervision was insufficient to such a degree they did not feel fully equipped with the appropriate skills and knowledge needed to carry out assessments.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In addition, this present study was able to reach beyond the scope of the Nicholls and Webster pilot study, as we also examined subsequent risk management plans. It is perhaps unsurprising we found problems in the quality of ARMS assessments, as in our earlier study, exploring police practitioners' experiences of completing ARMS assessments (Kewley, 2017); practitioners reported several issues with both the tool, and their own capacity to complete the assessment. Practitioners felt their training and supervision was insufficient to such a degree they did not feel fully equipped with the appropriate skills and knowledge needed to carry out assessments.…”
Section: Discussionmentioning
confidence: 66%
“…For example, this may be a result of assessor override (Wormith, Hogg, & Guzzo, 2010), noncompliance as a result of unmotivated practitioners, high stress levels or resourcing issues (Schafer & Williamson, 2018), a lack of assessor knowledge or poor training (Luong & Wormith, 2011), or a poorly constructed risk assessment tool etc. It was reported in an earlier study (Kewley, 2017) practitioners felt unskilled and undertrained when completing these assessments; this is likely to impact their motivation and ability to complete quality assessments. However, further exploration is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the work of Nicholls and Webster (2014) our research identified that ARMS was perceived to be a better classification tool than those used previously such as the RM2000. Supporting aspects of the work of Kewley (2017a) it is suggested that this was because ARMS enabled greater input into assessment, therefore a greater sense of control over the process and a feeling of protection from associated job troubles. Utilizing professional knowledge and being able to draw on their own experience and practice of working with sexual offenders enabled officers to make more professionally informed judgement calls in terms of classifying risk.…”
Section: Risk Classification Toolsmentioning
confidence: 99%
“…Recent evaluative research identified that practitioners viewed the tool positively because it did not rely solely of static factors and therefore enabled professional judgement and greater flexibility in identifying and changing offender risk (Kewley, 2017a; Nicholls and Webster, 2014). It could be argued that the use of ARMS appears more widely supported by practitioners as it affords them greater input in the classification process, thereby increasing a sense of control over the offender management process and reducing concerns about vulnerability to on-the-job and in-the-job troubles.…”
Section: Situational Decision Making and Sex Offender Classification mentioning
confidence: 99%